Mission, or no mission: factors behind knowledge of military language among Czech soldiers - Radková, Lucie; Mádrová , Jarmila; Místecký, Michal (Bohemistyka, 2022)
The goal of the study is to analyse the outcomes of a questionnaire survey which concerns understandability of military language used on former Afghanistan missions. Two groups of respondents took part in the survey – 50 soldiers with experience from a foreign mission, 50 soldiers without such experience. The data have indicated that when it comes to decoding randomly generated expressions, an important role is mainly played by the soldiers' other foreign missions, professional specialisations, length of service, and close contact with the participants of the Afghan missions.